Lipid profile in young people with newly diagnosed type 2 diabetes mellitus - A. K. Ovsyannikova; L. V. Shcherbakova; S. V. Mustafina; Yu. I. Ragino; D. V. Denisova; A. K. Kuntsevich; O. D. Rymar (Атеросклероз, 2018)
Diabetes mellitus (DM) is one of the most important not only medical but also social problems. With the development of vascular complications in people with diabetes in all age groups associated with the presence of dyslipidemia which is why these patients need to determine the lipid spectrum. In 30 patients aged 45 years with newly diagnosed type 2 diabetes (DM2) and in a control group comparable in sex, age and body mass index (BMI), the lipid profile was studied. Statistically significant differences were not detected not by one indicator between persons with hyperglycemia and with normoglycemia but the average levels of total cholesterol and low-density lipoprotein cholesterol were higher than the target values in both groups. There are no gender differences either. Perhaps this is due to a small amount of DM at which metabolic changes have not yet developed.